2011
DOI: 10.1021/op200051v
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Route Discovery and Introductory Optimization of a Novel Process to Idebenone

Abstract: An environmentally benign, convenient, high yielding, and cost-effective synthesis leading to idebenone is disclosed. The synthesis includes a bromination process for the preparation of 2-bromo-3,4,5-trimethoxy-1-methylbenzene, a protocol for the Heck cross-coupling reaction using either thermal or microwave heating, olefin reduction by palladium catalyzed hydrogenation, and a green oxidation protocol with hydrogen peroxide as oxidant to achieve the benzoquinone framework. The total synthesis is composed of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…To the best of our knowledge, there are little in the way of published papers associated with the heterocyclic-Coenzyme Q homologues; among the reported approaches, some used dangerous or toxic reagents (n-BuLi, Ag 2 O, Pd(PPh 3 ) 4 , etc. ), harsh reaction conditions, or multiple steps [9][10][11][12]22]. These drawbacks limited their wide application in industry and academia.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are little in the way of published papers associated with the heterocyclic-Coenzyme Q homologues; among the reported approaches, some used dangerous or toxic reagents (n-BuLi, Ag 2 O, Pd(PPh 3 ) 4 , etc. ), harsh reaction conditions, or multiple steps [9][10][11][12]22]. These drawbacks limited their wide application in industry and academia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] CoQ acts as a mobile electron carrier in the energy-transducing membranes of mitochondria and distributes the electrons between the various dehydrogenases and the cytochrome segments of the respiratory chain. [3][4][5][6] CoQ 10 (contains 10 isoprenyl units), the main homologue of CoQ existing in humans, is one of the most effective lipid-soluble antioxidants. CoQ 10 is widely used in the treatment of cardiovascular disease, hepatitis and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CoQ 10 is also sold as a drug or dietary supplement in many countries, and there is an increasing market demand. Many researches [3][4][5][6][7][8][9][10][11][12][13][14] have shown that some metabolites of CoQ 10 , and a number of synthetic CoQ analogues exhibit significant biological activities, such as inhibition of mitochondrial complex I, lipid peroxidation activity and blood platelet aggregation. Especially, some CoQ analogues with heterocyclic substituents could be developed as drugs, [12][13][14][15] so to find a simple and efficient synthetic route for its preparation is considerable incentive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20] The results from these studies combined with the recent achievements in membrane development spurred us to undertake the study disclosed herein with the goal to separate the target molecule from the Pd catalyst that was used in a Heck coupling reaction, [21] which was the key step of a new total synthesis of idebenone (8, Scheme 1, Step 2). [22] An important aspect of this project was to design and develop a green, efficient, and high yielding process. Moreover, the total synthesis should preferably involve readily available starting materials and cost-optimized synthetic methods because 8 is of potential industrial interest for use in pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%